(untitled) (Journal of Computational Mathematics, 1996)
A new sixth-order Runge-Kutta type method is developed for the numerical integration of the radial Schrödinger equation and of the coupled differential equations of the Schrödinger type. The formula developed contains certain free parameters which allows it to be fitted automatically to exponential functions. We give a comparative error analysis with other sixth order exponentially fitted methods. The theoretical and numerical results indicate that the new method is more accurate than the other exponentially fitted methods.